2023
DOI: 10.3389/fphys.2023.1077821
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dysbiosis gut microbiota and changes of neurotransmitters and short-chain fatty acids in valproic acid model rats

Abstract: Introduction: The microbiota–gut–brain axis plays an important role in the pathophysiology of autism spectrum disorder, but its specific mechanisms remain unclear. This study aimed to explore the associations of changes in neurotransmitters and short-chain fatty acids with alterations in gut microbiota in valproic acid model rats.Methods: The autism model rats were established by prenatal exposure to valproic acid (VPA). The Morris water maze test, open field test, and three-chamber test were conducted to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For example, Liu et al found that acetic acid and butyric acid were decreased in children with ASD ( 8 ). Besides, acetic acid, butyric acid, and valeric acid were significantly decreased in the fecal sample of a valproic acid model of ASD compared to those in the control group ( 31 ). However, the role of SCFAs in ASD pathology remains controversial.…”
Section: Discussionmentioning
confidence: 89%
“…For example, Liu et al found that acetic acid and butyric acid were decreased in children with ASD ( 8 ). Besides, acetic acid, butyric acid, and valeric acid were significantly decreased in the fecal sample of a valproic acid model of ASD compared to those in the control group ( 31 ). However, the role of SCFAs in ASD pathology remains controversial.…”
Section: Discussionmentioning
confidence: 89%
“…Also, many strains of Lactobacillus species are known to produce GABA, ACh and histamine [74] as well as tryptophan hydroxylase, the enzyme that catalyzes the rate-limiting step in the synthesis of serotonin. Further proof of associations between dysbiosis and changes in neurotransmitters and short-chain fatty acids were observed in a prenatal valproic acid model of ASD [75].…”
Section: Gut Microbiota -Neurotransmittersmentioning
confidence: 79%
“…Also, many strains of Lactobacillus species are known to produce GABA, ACh, and histamine [81], as well as tryptophan hydroxylase, the enzyme that catalyzes the rate-limiting step in the synthesis of serotonin. Further proof of associations between dysbiosis and changes in neurotransmitters and short-chain fatty acids was observed in a prenatal valproic acid model of ASD [82].…”
Section: Gut Microbiota-neurotransmittersmentioning
confidence: 82%